Peningkatan Kapasitas Keluarga Dalam Pelayanan Penyandang Disabilitas Berat Di Kota Tolitoli - Muhammad Iqbal; Mohammad Sawir; Ayu Lestari; Masrin Gafar; Nursifa Nursifa; Daniati Hi. Arsyad; Syarif Makmur (TOLIS MENGABDI : Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity aims to improve the knowledge, attitudes, and skills of PKH beneficiary families (KPM) in providing inclusive services for family members with severe disabilities. Using a family-based participatory approach, the intervention included the socialization of the P2K2 Social Welfare Disability Session module, practical simulations (role-play), reflective discussions, and follow-up mentoring conducted in Dadakitan Village, Buntuna Village, and Nalu Subdistrict with 373 participants. Data collection was conducted through pre-post questionnaires, observations, and short interviews; analysis was descriptive and triangulative. Results showed an increase in knowledge in 82% of participants, a change in attitude to be more empathetic in 76% of participants, more than 70% of participants were able to practice basic skills of disability-friendly services, and 90% expressed a commitment to implementing and disseminating these practices in their respective environments. The findings indicate that experiential learning and the involvement of local facilitators are effective in strengthening the capacity of families as primary service agents. It is recommended to expand the program's reach, strengthen collaboration with the Social Services and rehabilitation institutions, and provide post-activity assistance to ensure sustainability and integration of results into local policies.